Prevention and management of chemotherapy-induced polyneuropathy - Jordan, Berit; Jahn, Franziska; Sauer, Sandra; Jordan, Karin (Breast care, 2019)
Chemotherapy-induced peripheral neurotoxicity (CIPN) is a severe and common side effect caused by a variety of antineoplastic agents. Approximately 30-40% of patients treated with agents such as taxanes, vinca alkaloids, or platinum derivatives will develop CIPN. CIPN presents predominantly as a sensory axonal neuro(no)pathy with occasional motor and autonomic dysfunction exhibiting considerable variability of clinical symptoms ranging from mild tingling sensation to severe neuropathic pain. Typical symptoms include numbness (“minus symptom”), weakness, and abnormal gait as well as paresthesia and pain (“positive symptoms”). As CIPN symptoms potentially lead to long-term morbidity and can even aggravate after cessation of therapy, patients’ quality of life can be tremendously affected. In view of improved breast cancer survival outcomes, the late effects of CIPN are an unmet need in these patients. Therefore, early detection and assessment of first symptoms is important to effectively prevent severe CIPN. Therapeutic options for patients with CIPN are still limited, and pharmacological treatment focuses primarily on reduction or relief of neuropathic pain. CIPN is usually acutely managed by dose reduction or discontinuation of causative chemotherapy, potentially compromising treatment outcome. Currently, there is no causative proven therapy for the prevention of CIPN.
Gesehen am 22.08.2019